Early 20th Century Children's Interpretation: Strategies for Interpreting the Qur'an in Tamshiyyah al-Muslimin - Nur'aeni, Ulvah; Nuraini, Nabilah; Kamaruddin, Kasimah binti (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This research focuses on examining the strategy of interpreting the Qur'an for children in the early 20th century in the tafsir Tamshiyyah al-Muslimīn. The study of children's interpretation in the early 20th century is often missed. This is because the children's tafsir by KH Ahmad Sanusi (1888-1950) is presented in the interpretation of adult readers in the tafsir Tamshiyyah al-Muslimīn. The scarcity of children's tafsir studies in the early 20th century is because the production of tafsir at that time was still considered taboo and rarely studied in various pesantren. Although taught in some pesantren, tafsir material experienced exclusivity of readers. Bruinessen's research shows that tafsir can only be studied at the tsanawi to ulya level. This shows that the understanding of the Qur'an for children to beginner level is very limited. Whereas understanding religion through the teaching of the Qur'an for children is quite important to instill Islamic education since childhood. Another factor that causes children's interpretations to be quite rare is the limitations of printing technology and graphic design in children's interpretations in the early 20th century. At that time, most attractive graphic designs were only used for advertisements, packaging, and so on so that books or interpretive writings did not use such things. These limitations make early 20th century children's interpretations a unique and rare study. Therefore, this study aims to explore the strategies used by Sanusi in presenting the learning and meaning of the Qur'an for children at that time amid the lack of tafsir production, the exclusivity of children's tafsir readers, and the limitations of printing technology and graphic design for children's tafsir readers. The findings of this study conclude that the strategy used by Sanusi in interpreting the Qur'an for children is by using verbal illustrations, transliteration of the Qur'an, local language adaptation and verse grouping. Comparative approach and content analysis are used to explore the findings. Penelitian ini fokus mengkaji strategi penafsiran al-Qur’an untuk anak di awal abad 20 dalam tafsir Tamshiyyah al-Muslimīn. Kajian tafsir anak di awal abad 20 seringkali terlewat. Ini karena tafsir anak karya KH. Ahmad Sanusi (1888-1950) disajikan dalam tafsir pembaca dewasa dalam tafsir Tamshiyyah al-Muslimīn. Kebanyakan tafsir anak yang menjadi objek penelitian selama ini adalah tafsir anak yang terbit abad 21. Langkanya kajian tafsir anak awal abad 20 ini dikarenakan produksi tafsir di masa itu masih dianggap tabu dan jarang dipelajari di berbagai pesantren. Meskipun diajarkan di beberapa pesantren, materi tafsir mengalami eksklusivitas pembaca. Penelitian Bruinessen tafsir hanya boleh dipelajari pada level tsanawi hingga ulya. Ini menunjukkan pemahaman al-Qur’an bagi tingkat anak-anak hingga pemula sangat terbatas. Padahal pemahaman agama melalui pengajaran al-Qur’an bagi anak cukup penting untuk menanamkan pendidikan Islam sejak kecil. Faktor lainnya yang menyebabkan tafsir anak cukup langka adalah keterbatasan teknonologi percetakan dan desain grafis pada tafsir anak di awal abad 20. Pada masa itu, kebanyakan desain grafis yang menarik hanya digunakan untuk iklan, kemasan, dan sebagainya sehingga buku atau karya tulis yang bersifat interpretatif tidak menggunakan hal yang demikian. Beberapa faktor keterbatasan ini yang menjadikan tafsir anak awal abad 20 merupakan penelitian yang unik dan langka dikaji. Oleh karena itu, penelitian ini bertujuan untuk menggali strategi yang digunakan oleh Sanusi dalam menghadirkan pembelajaran dan pemaknaan al-Qur’an bagi anak di masa itu di tengah minimnya produksi tafsir, eksklusivitas pembaca tafsir anak, serta keterbatasan teknologi percetakan dan desain grafis untuk tafsir pembaca anak. Temuan penelitian ini menyimpulkan strategi yang digunakan oleh Sanusi dalam penafsiran al-Qur’an untuk anak yaitu dengan menggunakan ilustrasi verbal, transliterasi al-Qur’an, adaptasi bahasa lokal dan peneglompokan ayat. Pendekatan komparatif dan analisis konten digunakan untuk menggali temuan tersebut.